The Exploration of Nusantara’s Local Wisdom Through Bahasa Indonesia Untuk Kita (Bikta) for Diaspora Children at the Indonesian Embassy in Doha Qatar - Octo Dendy Andriyanto; Meilita Hardika; Darni Darni; Sukarman Sukarman; Yohan Susilo; Pensri Panich (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study explores the initial abilities of BIPA (Indonesian Language for Foreign Speakers) students and the BIPA learning process with Nusantara’s local wisdom in the BIKTA program for diaspora children at the Indonesian Embassy in Doha, Qatar. This research has an urgency in exploring Nusantara’s local wisdom through BIPA learning. This is based on the concern that the diaspora of Indonesian children in Qatar has minimal knowledge of Indonesian culture. Through this research, it is hoped that it can contribute to developing Indonesian insights through exploration of Nusantara’s local wisdom through BIPA learning. The method in this study uses qualitative research. Research data collection was carried out by observation, questionnaires, and FGDs for teachers and program administrators. The research results on the initial abilities of BIPA students at the Indonesian Embassy in Doha are quite varied and divided at the BIPA I, BIPA II, and BIPA III levels. The BIPA learning process explores local wisdom including traditional musical instruments, national songs, Indonesian folklore and legends, food, and Indonesian tourism.